Polarized modulation and receivers for wireless communication. Issue 1 (March 2021) - Raja Kumar, R.; Pandian, R.; Puja, N.K.; Indumathi, P.
Abstract: Achieving increase in spectral efficiency has always been a major aspect in communication systems. Our work emphasises the application of dual polarized modulation in a wireless environment. Our main goal is to increase the throughput of the system. We aim to increase the spectral efficiency and throughput without an increment of radiated energy without any Channel State Information at Transmitter (CSIT) and feedback at the transmitter The proposed dual Polarized Modulation (DPMOD) scheme exploits the polarization diversity reducing the required SNR (Eb/N0) and adding an extra bit and achieves the same Bit Error Rate (BER) carrying extra information.